Prescribing Experience: Discussion of Recreational Therapy as Health Care. (3rd July 2017) - Baker, Dana Lee; Dye, Cadie
ABSTRACT: Health care extends beyond pills and medical devices. Truncated conceptions of health care can be particularly challenging for disabled people and people with disabilities. This truth resonates even deeper given that the roles of spirituality, religion, and the wellbeing of the whole person occupy the central role of health care. Despite hard-won advances in parity of coverage and in health promotion, prescriptions and coverage of care beyond medication and devices still strike many as less within the role of medical providers. The authors explore public discourse as reflected in state agency websites and in blogs surrounding two forms of therapy during the time of the design and early implementation of the Patient Protection and Affordable Care Act.